Congenital mesoblastic nephroma: Its diverse clinical features – A literature review with a case report. (2nd April 2016) - Takahashi, H.; Ohkuchi, A.; Kuwata, T.; Usui, R.; Takahashi, S.; Matsubara, S.
Abstract : To characterise congenital mesoblastic nephroma (CMN), with special emphasis on polyhydramnios and the neonatal prognosis, we summarise 31 CMN patients (30 reported patients and the present patient). CMN was detected at a median of 30 weeks' gestation, and infants were delivered at a median of 34 weeks' gestation. Of 27 patients with available data, 19 (70%) had polyhydramnios, of which 8 required amnio- drainage. Women with amnio-drainage gave birth significantly earlier (30.4 weeks' gestation) than those without polyhydramnios (36.7 weeks' gestation). Thus, CMN was frequently associated with polyhydramnios and this polyhydramnios was associated with a significant increase in the risk of preterm birth. Of 20 patients with available data, the affected-side kidney was 'compressed' in 16 and 'replaced' in 4: polyhydramnios was present in a half vs 100%, respectively, suggesting that a 'replaced' kidney may suggest a more aggressive tumour and may be associated with a poorer prognosis. Univariate analysis showed that early gestational week at diagnosis was the only feature significantly associated with poor prognosis. Thus, polyhydramnios, 'replaced' kidney and early gestational week at diagnosis, may indicate poor prognosis, to which obstetricians should pay attention.